A novel ultrasonic cavitation assisted fluid jet polishing system. Issue 1 (2017) - Beaucamp, Anthony; Katsuura, Tomoya; Kawara, Zensaku
Abstract: Fluid jet polishing is a versatile process used for super-fine finishing of small and complex optical and prosthetic surfaces. Advantages of this process include highly controllable sub-millimetre polishing footprints and absence of tool wear, though the main drawback is very low material removal rate. To address this issue, a novel system was developed in which ultrasonic cavitation causes micro-bubble generation directly upstream of the nozzle outlet. Experimental data shows that these micro-bubbles boost removal rate by up-to 380%, without causing any degradation of the surface finish. This paper reports on the modelling, implementation, and testing of this new polishing system.